2014
DOI: 10.1038/nphoton.2014.280
|View full text |Cite
|
Sign up to set email alerts
|

Photon number resolution enables quantum receiver for realistic coherent optical communications

Abstract: Quantum-enhanced measurements can provide information about the properties of a physical system with sensitivities beyond what is fundamentally possible with conventional technologies. However, this advantage can be achieved only if quantum measurement technologies are robust against losses and real-world imperfections, and can operate in regimes compatible with existing systems. Here, we demonstrate a quantum receiver for coherent communication, the performance of which not only surpasses the standard quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
161
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(162 citation statements)
references
References 43 publications
1
161
0
Order By: Relevance
“…In particular, the required SFG can be implemented in an optical cavity or nonlinear waveguides [60], and its K cycles can be combined on a photonic integrated circuit [61][62][63]. Feed-forward operations have been successfully employed to obtain improved performance in the discrimination of coherent states [39][40][41], mixed states [64], and entangled states [65]. Furthermore, our receivers have other potential applications, including optimum reception for the QI communication protocol [66], and quantum state and channel tomography [67,68].…”
Section: Prl 118 040801 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the required SFG can be implemented in an optical cavity or nonlinear waveguides [60], and its K cycles can be combined on a photonic integrated circuit [61][62][63]. Feed-forward operations have been successfully employed to obtain improved performance in the discrimination of coherent states [39][40][41], mixed states [64], and entangled states [65]. Furthermore, our receivers have other potential applications, including optimum reception for the QI communication protocol [66], and quantum state and channel tomography [67,68].…”
Section: Prl 118 040801 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…Adding a feedforward (FF) mechanism yields the FF-SFG receiver, whose error probability achieves the Helstrom bound [33]. The FF-SFG receiver is potentially promising for other quantum-enhanced sensing scenarios, such as phase estimation, and it enlarges the toolbox for quantum-state discrimination [34][35][36][37][38][39][40][41][42][43][44][45][46][47]. In particular, it is the first architecture-short of a quantum computer-for optimum discrimination of multimode Gaussian mixed states, a major step beyond the optimum discrimination of singlemode pure states [48][49][50][51].…”
mentioning
confidence: 99%
“…It has also been reported that separable m easurem ents w ith feedforw ard im proves the sensitivity in discrim inating code w ords so as to approach the Holevo bound. There has been experim ental dem onstration o f joint-detection receivers w hich discrim inate code w ords encoded as sequences o f coherent states, with error rates below the standard quantum lim it achievable w ith hetero dyne m easurem ent [22,23]. Building upon the results o f our current work, we plan to investigate G aussian com m unications involving collective operations.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is one of the innermost consequences of the laws of quantum mechanics that nonorthogonal states cannot be discriminated with certainty. Optimal detection strategies were first investigated by Helstrom [20,21] and Holevo [22] and a lot of attention has since been devoted to the development of optimal and near-optimal receivers for binary coherent states [23][24][25][26][27][28][29][30][31][32] and for the discrimination of larger signal alphabets [33][34][35][36][37][38][39][40][41]. An overview over different receiver schemes is provided in Appendix B.…”
Section: Binary Coherent-state Cloningmentioning
confidence: 99%